Street Vended Foods and Associated Environment in Two Major Cities of India: Microbial Safety Concern - Shagufta Bi; Dubal, Zunjar Baburao; Bhilegaonkar, Kiran Narayan; Anukampa; Sivakumar M.; Zende, Ravindra Jayavant; Vaidya, Vilas Mahadev (International Journal of Livestock Research, 2018)
Majority of the people in the cities liked to have street food even with the compromising their health. Therefore, the present study was carried out to find out the microbiological profile/safety of street vended foods and associated environmental samples collected from Mumbai and Delhi. A total of 166 samples of foods of animal origin (124) and associated environmental samples (42) were processed for aerobic plate count, enumeration of Escherichia coli, Staphylococcus spp., sulphite reducing Clostridia (SRC) and for detection of Salmonella spp. and Listeria monocytogenes, while water samples tested for most probable number. Swab samples showed low to marginal APC for Delhi while marginal to high in Mumbai. Notably, E. coli and Staphylococcus spp. count is higher in table and cloth swabs. Overall, 42.4%, 69.6% and 51.5% swab samples were positive for E. coli, Staphylococcus spp. and SRC, respectively. APC for raw chicken was 5.00 ± 0.17 & 5.45 ± 0.05 log10cfu g-1 for Mumbai and Delhi, respectively while that of 4.13 ± 0.18 and 4.53 ± 0.10 log cfu g-1 for raw egg and raw milk from Delhi and 4.00 log cfu g-1 for raw egg from Mumbai. Salad and chutney samples showed marginal to high APC (3.5 to 4.7 log cfu g-1) with the presence of E. coli and Staphylococcus spp. in majority of the samples in both the cities. Overall, 38.75, 51.25 and 35.0% raw foods; 52.0, 36.0 and 8.0% milk products and 22.72, 31.81 and 13.63% cooked food samples were positive for E. coli, Staphylococcus spp. and SRC, respectively. Salmonella spp. was present in only one chutney sample while L. monocytogenes was absent in all. Cooked chicken from Mumbai had 1.89 ± 0.56 log cfu g-1 with mean E. coli and Staphylococcal count is <1.6 log cfu g-1. Boiled egg, omelette and boiled milk also had limited microbial load (APC) with majority of the samples free from E. coli, Staphylococcus spp. and SRC. Only 2/9 water samples have high MPN count. Of the 80 Staphylococcus spp. isolates, 23 (28.75%) were found to be positive for nuc and coa genes in PCR indicated as S. aureus with an overall presence of 14.64%. Though the microbiological quality of all cooked products was found good except for one sample, proper sanitation, hygienic environment, good hygienic raw food, clean water supply and personnel sanitation should be adopted while doing the street vending operations.